Cytogenetic characterization of F1, F2 and backcross hybrids of the Neotropical catfish species Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum (Pimelodidae, Siluriformes) - Prado, Fernanda Dotti do [UNESP] (2012)
The cytogenetic characteristics of Pseudoplatystoma corruscans and Pseudoplatystoma reticulatum and their F1, F2 and backcross hybrids were assessed by using chromosome banding techniques. The diploid number of 56 chromosomes was constant in all species and lineages, with a karyotypic formula containing 20 metacentric, 12 submetacentric, 12 subtelocentric and 12 acrocentric chromosomes. Nucleolar organizer regions (NORs) were identified in two subtelocentric chromosomes in the parents and hybrids, with partial nucleolar dominance in F1 and F2 specimens. Heterochromatic blocks were detected in the terminal and centromeric regions of some chromosomes in all individuals. For parental and hybrid lineages, 18S ribosomal clusters corresponding to NORs and 5S ribosomal genes were identified in distinct pairs of chromosomes. The striking conservation in the chromosomal macrostructure of the parental species may account for the fertility of their F1 hybrids. Similarly, the lack of marked alterations in the chromosomal structure of the F1 hybrids could account for the maintenance of these features in post-F1 lineages.